Rational Pharmacotherapy and Correction of Immunity Disorders in Children with Chronic Hepatitis (Clinical Review) - L. G. Goryacheva; M. G. Romantsov; S. G. Agaeva; YU. N. Linkov; A. L. Kovalenko (Антибиотики и Химиотерапия)
The data on the efficacy of antivirals and their impact on the virologic and immunologic indices in HCV- and HBV-infected children are presented. The best therapeutic effect in the management of children with chronic virus hepatitis was provided by combined antiviral therapy of different action. In the treatment of babies the drugs of choice could be viferon or cycloferon, for the 2-year older children with chronic hepatitis B the combination of viferon + cycloferon should be recommended and for those with chronic hepatitis C the combination of interal + cycloferon could be used. The cycloferon combination with interferons-а makes it possible to generate the Th1 cellular immune response, to minimize the side effects of interferons and chemotherapeutics and to improve their tolerability. The complex therapy of patients with chronic hepatitis B and lambliasis, using cycloferon and macmiror, provided stable effect, less frequent relapses of lambliasis and minimum side effects of the specific therapy. The repeated isolation of lamblia within a 1-year observation period was recorded only in 16.6% of the children treated with cycloferon vs. the control (40.0%).